The Normative Features of Creativity: Creative Individuals are Judged to be Warmer and More Competent. (11th November 2020) - Bonetto, Eric; Pichot, Nicolas; Girandola, Fabien; Bonnardel, Nathalie
Abstract: Many studies mention the social valorization of creative individuals. However, previous works show contrasting results concerning both this valorization and the links between creativity and the two dimensions of social judgment (individuals' warmth and competence). Consequently, we implemented two paradigms classically used when examining the normative features of individuals' traits such as creativity. Study 1 ( N = 206), using a self‐presentation paradigm, showed that individuals tend to present themselves as creative in order to gain others' approval. Thus, creativity seems to be subject to social valorization. Studies 2 ( N = 149) and 3 ( N = 457), using social judgment tasks, corroborated these findings, and allowed to gain a finer‐grained vision of what dimensions of social value are associated with creativity. These ones showed that highly creative individuals were considered warmer and more competent than weakly creative individuals. Results from Study 3 also suggest that these judgments may be domain‐dependent. Implications for research on creativity, as well as on social judgment, are discussed.